Claroscura Representation: An Audio-visual and Theoretical Exploration of the Representation of the Past Through Documentary Filmmaking - Gerrit Stollbrock Trujillo (Íconos)
At the nexus between audio-visual production and theoretical research, this article is based on the experience of producing a documentary on the history of a cement plant in Colombia: La Siberia. The tensions between the narratives constructed in the documentary and the immensity of the discarded archives from the plant drive a theoretical quest to respond to its own iconoclast and the post-structuralist critique of history. This brought us to the formulation of the concept of claroscura representation, defined as representation that is transparent about its own limitations. I put this concept to the test through the medium of documentary film, talking specifically about the making of La Siberia, and suggest its relevance in other projects that attempt to represent the past or history through film. I suggest that this theory drives us towards the formulation of a new artistic project. The research process, and the dialogue between theory and practice, is interpreted using the model of abduction proposed by Charles Sanders Peirce.